The Application of Fluorescence Microscopy and Scanning Electron Microscopy in the Detection of Delayed Ettringite Formation in Concrete - Matos, L. (2010)
Submitted by António Santos Silva (ssilva@lnec.pt) on 2010-04-07T13:05:53Z No. of bitstreams: 1 Lina_ et al_MSF.636-637.1266[1].pdf: 3261952 bytes, checksum: c085beb6bfa288b88f2359aabcc87258 (MD5)